Information needs of users patronizing the National Archives of Malaysia / Kaszilawati Kasman - Kaszilawati , Kasman (2020)
The National Archives of Malaysia has a vision of becoming the centre of excellence for information sources and services by the year 2020. This vision is a support to make Malaysia a developed nation with strong moral and ethical values through the national heritage. The literature indicates that in an archival context, user studies remain unlimited. Even in Malaysia, archival user study, especially on archival user information needs, have not been empirically investigated. In order for archivists to respond adequately to the needs of researchers using their services, they must first understand the kinds of information which particular user group requires. This study is designed to help the National Archives of Malaysia identify the information needs of the users so that the National Archives of Malaysia can serve them effectively and more efficiently. For that purpose, this study explored the information needs of users while using archives or archival materials as their primary sources of information, and discovered the users actual use of primary sources. In this regard, the headquarters of the National Archives of Malaysia, Jalan Sultan Abdul Halim, Kuala Lumpur has been chosen as the case setting. This study used a qualitative data gathering technique using interviews. Observation and document analysis were also employed for data collection. All registered researchers who patronized the National Archives of Malaysia served as survey population and a total of 20 participants were purposively sampled. The qualitative data were analyzed descriptively and results were presented narratively. The results of this study found that archival user information needs to be categorized into 5 main areas: purpose of archive information needs, popular archive information subject, preferred type of archived material, reasons leading to visit the National Archives of Malaysia and archives’ user concern in obtaining required information. Finally, this study gives additional input on how the crucial role of the National Archives of Malaysia may be strengthened to provide sufficient archives information and convenient facilities for its users. The findings can then be utilized by archivists in their efforts to respond more effectively to the needs of this particular group of archival users.